Detection of bovine milk–, but likely not soy–derived, peptides in human milk after maternal consumption of bovine milk and soy beverage: a randomized, cross-over, dietary intervention trial - Partridge, Cassandra L.; Paullin, Trillitye R.; Kim, Bum Jin; Dallas, David C.; Williams, Janet E.; McGuire, Mark A.; Kaur, Harpreet; McGuire, Michelle K. (Frontiers in Nutrition, 2025)
BackgroundFood-borne allergens in human milk (HM) may cause allergic responses in HM-fed infants, but variability of allergen transfer complicates recommendations for individuals nursing food-allergic infants.ObjectiveWe aimed to identify bovine- and soy-derived peptides in HM after maternal elimination and reintroduction of bovine milk (BM) and soy beverage (SB).MethodsIn this randomized, cross-over, dietary intervention trial, 38 lactating participants underwent 2 study phases, each including a 5-day diet elimination, 3-day diet intervention, and 2-day washout. Each diet intervention required daily consumption of increasing amounts of BM or SB (175, 295, and 415 mL). Peptidomics analysis was performed on a subset of HM samples (24 participants) collected after dietary elimination, and 2 and 4 h after BM/SB consumption (415 mL). Peptides were isolated via ethanol precipitation and C18 solid-phase extraction, analyzed by LC–MS/MS, and identified with Proteome Discoverer.ResultsWe identified 121 bovine-derived peptides (associated with 6 proteins) in HM collected during the BM phase. From most to least abundant, these proteins were β-lactoglobulin, κ-casein, αs1-casein, β-casein, α-lactalbumin protein variant D, and glycosylation-dependent cell adhesion molecule 1. Generalized linear mixed models demonstrated differences in relative abundance for 14 peptides when comparing before, and 2 and 4 h after BM consumption. We identified 8 peptides of possible soy origin in HM collected during the SB phase, but they were not matched to parent proteins with adequate confidence.ConclusionThe relative abundance of some BM-derived peptides, while low overall, may differ in human milk collected after maternal BM dietary elimination compared to 2 and 4 h after BM consumption. Five days of dietary elimination may not be adequate for the elimination of BM-derived peptides or low levels of these non-human peptides may be present in HM from other sources. No confident soy-derived peptides from the SB were identified in HM after consumption.Clinical trial registrationhttps://clinicaltrials.gov/study/NCT04851340, identifier NCT04851340.